Ideais formativos de homem da emissora de Educação Rural de Caicó (Rio Grande do Norte, 1963-1978) - Medeiros, Mário Lourenço de (2008)
Under the aegis of the third diocese bishop of Caicó, Dom Manuel Tavares de Araújo, the Broadcasting Station of Rural Education of that city was founded, in May 1 s" 1963 with the ideal of being then an educational city, preferentially for youths and adults, rural meu and women of the arca of Seridó in Rio Grande do Norte state. In the year of its 40th birthday (2003), we began the investigation of that radio station choosing as study object its educational and formative programming, in the inc1usion of the first fifteen years of its existence (1963-1978), period that reaches the official inauguration of the Radio Station and the end of the bishopric of its fOllllder as Bishop of Caicó. Elucidating and showing Man's formative ideaIs longed by that Catholic educational broadcasting station, underlying to its radiophonic programming, such as the idealization for it reached, is the objective of this Doctorate work. It was considered pertinent to discover the guidelines that historically have permeated the Social Doçtrine of the Catholic Church addressing its aggiornamento, especially in what concerns to the employment of the modern ways of communication for the distance with the aim of evangelizing and educating. In arder to understand the ideaIs of the investigated educational Radio, we have delimited the research to the thematic Catholic Church, means of social communication and base education. In face of the study object and the aim to be reached it was appealed, methodologically, to the notion of cultural action present in Certeau (1995), and to the understanding of educational formation backgrounded fIam the modern thinkers that discuss it. Such frame references have allowed us to analyze in a wider spectrum tl)e programming broadcasted on the air by the sound wavys of that educ(itional Çatholic Radio, as well as, the very acts of cultural idealizations that has orientated it in its foundations. The thesis here defended is that. the Radio, at procJaiming itself as a broadcasting station of rural education directed preferably to the rural sertanejo countrymen, without neglecting its admitted ends, has surpassed them in its overall range. It was identified an articulate approach of its programmatic modules with the guid,elines emanateq from the Catholic Teaching about the use of the. means of social communication. At conceiving, establishin,g and executing an ec1ectic programmatic and div,ersified grating, the Rural Radio of Caicó has transcended to a strict human-Christian formation to request the development of the human, spiritual and cQrporaldimensions, jointly. With suchprogramming, it addressed to the seridoenses as real meu and women inserted in the "sertanej.o" environment with effective structural and existential problems of alI types, induding the hunger, the thirst, the syndical organization, the cQoperativism, the colIective modero work and the absence of universalizing school education. Its radiophonic transmissions, I}lled by the demands of an enlarged, open, dialogic and responsible communication, wheneIllbracing dedicated modules to religious and catechetical emissions, to the entertainment, to the radiojoumalism, to the country root culture, and to the school education of b se for the modality of the School and of the radiophonic classes, subsumed to ideaIs that longed for the formation of a multifaceted and pluridimensional sertanejo Man; of men and women that, without abjuring the Catholicism, were able to understand, to dialogued and to live together with the general demands of a society in progressive mutation, whose economical, social, cultural and educational demands it IDade themselves to be felt through the sertão potiguar of the Serido region, equal way of the intemationalized world